2008
DOI: 10.1002/chem.200701300
|View full text |Cite
|
Sign up to set email alerts
|

Half‐Sandwich oN,N‐Dimethylaminobenzyl Complexes over the Full Size Range of Group 3 and Lanthanide Metals. Synthesis, Structural Characterization, and Catalysis of Phosphine PH Bond Addition to Carbodiimides

Abstract: The acid-base reactions between the rare-earth metal (Ln) tris(ortho-N,N-dimethylaminobenzyl) complexes [Ln(CH2C(H4NMe2-o)3] with one equivalent of the silylene-linked cyclopentadiene-amine ligand (C5Me4H)SiMe2NH(C6H2Me3-2,4,6) afforded the corresponding half-sandwich aminobenzyl complexes [{Me2Si(C5Me4)(NC6H2Me3-2,4,6)}Ln(CH2C6H4NMe2-o)(thf)] (2-Ln) (Ln=Y, La, Pr, Nd, Sm, Gd, Lu) in 60-87 % isolated yields. The one-pot reaction between ScCl(3) and [Me2Si(C5Me4)(NC6H2Me3-2,4,6)]Li2 followed by reaction with Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 46 publications
2
81
0
Order By: Relevance
“…Five years after the report on the syntheses and structures of La(DMA) 3 and Y(DMA) 3 [10], many intermediate members in the Ln(DMA) 3 family have been prepared and were shown to form isomorphous crystals [12][13][14]. Although this series of complexes is not as reactive as the unstabilized Ln(Bn) 3 complexes, they are reactive enough for further functionalization (vide infra).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five years after the report on the syntheses and structures of La(DMA) 3 and Y(DMA) 3 [10], many intermediate members in the Ln(DMA) 3 family have been prepared and were shown to form isomorphous crystals [12][13][14]. Although this series of complexes is not as reactive as the unstabilized Ln(Bn) 3 complexes, they are reactive enough for further functionalization (vide infra).…”
Section: Methodsmentioning
confidence: 99%
“…This increased the crystalline yield from 41 % up to 87 % and gave good yields for other metals like Pr and Nd (92 % and 83 %, respectively) [14]. It was further found that reaction of LnCl 3 precursors with Li(DMA) also gave satisfactory crystalline yields for the metals Y (75 %), Sm (92 %), Gd (85 %) and Lu (77 %) [14]. Also Xie et al report that Y(DMA) 3 and Er(DMA) 3 have been prepared from LnCl 3 and Li(DMA) in yields of 81 % and 55 %, respectively [20].…”
Section: Synthesesmentioning
confidence: 96%
“…In most cases, the desired complexes [Ln(CH 2 C 6 H 4 NMe 2 -o){Me 2 Si(C 5 Me 4 )-(NC 6 H 2 Me 3 -2,4,6)}(thf)] (13-Ln: Ln = Y, La, Pr, Nd, Sm, Gd, and Lu) can be easily prepared by the reaction of [Ln(CH 2 C 6 H 4 NMe 2 -o) 3 ] with the corresponding cyclopentadienylamine ligands (Scheme 23). 26 However, in the case of scandium (13-Sc) (the smallest ion in the rare earth series), the one-pot metathetical reactions of ScCl 3 (thf) 3 with 1 equivalent of the dilithium salt of the ligand and 1 equivalent of LiCH 2 C 6 H 4 NMe 2 -o prove to be a more appropriate synthetic route (Scheme 23). 26 …”
Section: 25mentioning
confidence: 99%
“…26 However, in the case of scandium (13-Sc) (the smallest ion in the rare earth series), the one-pot metathetical reactions of ScCl 3 (thf) 3 with 1 equivalent of the dilithium salt of the ligand and 1 equivalent of LiCH 2 C 6 H 4 NMe 2 -o prove to be a more appropriate synthetic route (Scheme 23). 26 …”
Section: 25mentioning
confidence: 99%
See 1 more Smart Citation